Fragility of resale markets for securitized assets and policy of asset purchases - Martin Kuncl (Bank of Canada, 2016)
Markets for securitized assets were characterized by high liquidity prior to the recent financial crisis and by a sudden market dry-up at the onset of the crisis. A general equilibrium model with heterogeneous investment opportunities and information frictions predicts that, in boom periods or mild recessions, the degree of adverse selection in resale markets for securitized assets is limited because of the reputation-based guarantees by asset originators. This supports investment and output. However, in a deep recession, characterized by high dispersion of asset qualities, there is a sudden surge in adverse selection due to an economy-wide default on reputation-based guarantees, which persistently depresses the output in the economy. Government policy of asset purchases limits the negative effects of adverse selection on the real economy, but may create a negative moral hazard problem.
Keywords: E32; E5; G01; G2; 330; Business fluctuations and cycles; Economic models; Credit and credit aggregates; Financial markets; Financial stability; Financial system regulation and policies